(3GdfLOjGJ aj GdfSHs - (3eMeO Hf CMeO Hf eMeO GdbQTj GdCehj, CHh GdeXaQ, (B507 (3g`s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3GdhbJ MGVQ GdHOjgI Yf GdCUeYi bGd bGd di GdQTjO jhekG jG CUeYi CJYQa ddYQH EYJPGQkG Ch fOekG s
(3BNQgG (B:s
(3heG CQSdfG ef QShd EdG HdSGf bheg Je GdcJGH HYhf Gddg s
(3GdcJGH fGbU GdChd hHg WeS ai GdfgGjI hdGjYQa gd gPG gh GdfLOjGJ Ce TQM dgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B209s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1930s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs